Analisis Perkembangan UMKM Binaan yang Memperoleh Kredit Wibawa dari Dinas Koperasi dan UMKM Kota Semarang - Nurul Hidayah; Achma Hendra Setiawan (Universitas Diponegoro, 2020)
Micro, small and medium enterprises (MSMEs) have a strategic role in Indonesia's economic growth and development.MSME also has an important role in driving the economic growth of Semarang City. However, capital constraints are still a classic problem that is hampering the progress of MSMEs. Semarang City Government through the Cooperative and UMKM Office has released a loan program called Wibawa Credit. The purpose of this study is to analyze the changes in sales turnover, operating income, number of buyers or customers and working hours at MSMEs before and after obtaining the Credit Authority. The validity and reliability test results show that the questionnaire distributed to 85 respondents was valid and reliable. On the results of the Wilcoxon Signed Rank Test of 85 respondents appears that the level of significance shows <0.05, which means that there are significant differences, such as the difference in the level of sales turnover, operating income, the number of buyers or customers and working hours after obtaining Wibawa credit from the Semarang City Cooperative and MSMEs Office. The differences are in the forms of an increase in sales turnover by 50.69 percent, an increase in operating profit by 48.82 percent, an increase in the number of buyers or customers by 33.4 percent, and an increase in working hours by 14.81 percent.